2017
DOI: 10.1111/odi.12620
|View full text |Cite
|
Sign up to set email alerts
|

An update on the implications of cyclin D1 in oral carcinogenesis

Abstract: Cyclin D1 promotes cell cycle progression during G1 phase, a key event in G1-S transition. The protein is encoded by gene CCND1, located in chromosomal band 11q13. Cyclin D1 plays key roles in cell biology, including cell proliferation and growth regulation, mitochondrial activity modulation, DNA repair, and cell migration control. CCND1 gene and its protein cyclin D1 are frequently altered by different molecular mechanisms, including amplification, chromosomal translocations, mutations, and activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 127 publications
(305 reference statements)
5
77
0
Order By: Relevance
“…We also found that cyclin D1 expression was significantly correlated with both CDK4 and CDK6 expression. Our findings are supportive of the notion that cyclin D1 partners CDK4/6 in oral carcinogenesis; however, other reports have shown that overexpression of cyclin D1 may contribute to tumour progression independent of CDK4 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that cyclin D1 expression was significantly correlated with both CDK4 and CDK6 expression. Our findings are supportive of the notion that cyclin D1 partners CDK4/6 in oral carcinogenesis; however, other reports have shown that overexpression of cyclin D1 may contribute to tumour progression independent of CDK4 …”
Section: Discussionsupporting
confidence: 92%
“…This result is concordant with a previous study by Patel et al, where they analysed 60 samples and found that the expression of p63 and cyclin D1 increased as the grade of dysplasia increased . Moreover, cyclin D1 overexpression has been associated with factors that indicate a poor prognosis, such as lymph node involvement and lack of response to treatment . In the present study, we were unable to check such a correlation due to the lack of clinical follow‐up data.…”
Section: Discussionsupporting
confidence: 90%
“…CCND1 is able to form a ternary complex with cyclin‐dependent kinases CDK4 and CDK6 to phosphorylate Rb and release E2F transcription factors, thus facilitating G1/S transition . It has been well documented that CCND1 is a proto‐oncogene that is frequently overexpressed in various human cancers, including LSCC . Dysregulation of CCND1 can lead to uncontrolled cell proliferation and malignancy, which enables it to be a feasible and effective therapeutic target for cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 (CD1) is a protein encoded by the CCND1 gene, located in chromosomal band 11q13, which promotes cell cycle progression from G1 to S phase (Sherr & Roberts, ). Its expression is frequently altered in human cancer, especially in oral squamous cell carcinoma (OSCC) (Ramos‐García, Gil‐Montoya et al., ). Gene amplification is the most important overexpression mechanism in OSCC, with an amplification rate more than twofold higher than observed in other cancers (Ramos‐García, Ruiz‐Ávila et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene amplification is the most important overexpression mechanism in OSCC, with an amplification rate more than twofold higher than observed in other cancers (Ramos‐García, Ruiz‐Ávila et al., ). CD1 overexpression is often associated with indicators of a poor prognosis, including high T and N stage, advanced stage, and poor differentiation, and with non‐response to treatment and reduced survival, suggesting that CD1 may play a key role in oral carcinogenesis (Ramos‐García, Gil‐Montoya et al., ).…”
Section: Introductionmentioning
confidence: 99%